Vietnamese English Language Teachers' Perspectives on Teaching and Learning in the Asia-Pacific Region - Dobinson, Toni (University of Danang, 2013)
Much has been written about approaches to teaching and learning, the 'good' teacher, the 'good' learner and in particular how notions of these may differ regionally. Even more focus has been placed upon the links between culture, pedagogy and learning practices especially with learners from Asian backgrounds.This article documents responses, reflections and narratives collected from 10 Vietnamese English language teachers on site in Ho Chi Min City, Vietnam in an interpretivist-interactionist study which was qualitative in its approach. Through the use of semi-structured interviews, participants reflected upon what made a 'good' teacher and a 'good' learner concluding, on the whole, that personal characteristics are as important as technique or strategy. Some participants also reported having mixed feelings about Western educational theory and related teaching practices and were either critical of notions of Asians as reproductive, passive and uncritical in their learning approach or offered insights into the reasons for these approaches to learning.